2018
DOI: 10.1093/jas/sky344
|View full text |Cite
|
Sign up to set email alerts
|

Energy content and nutrient digestibility of diets containing Lactobacillus-fermented barley or wheat fed to weaned pigs

Abstract: This study was conducted to determine the energy content and apparent total tract digestibility (ATTD) of nutrients of diets containing Lactobacillus-fermented barley or wheat fed to weaned pigs. Thirty-six weaned pigs (8.14 ± 0.65 kg of body weight) were randomly assigned to 1 of 6 diets in a completely randomized design to give 6 replicates per diet. Pigs were individually housed in metabolism crates to determine digestible energy and metabolizable energy contents. Net energy was also calculated from the ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Researches have shown that oral administration of L. plantarum can improve the immune responses and enhance the intestinal barrier function of weaning piglets (Wang, Ji, et al, ; Yang, Jiang, Zheng, Wang, & Yang, ). Diet with L. plantarum ‐fermented wheat also can improve the apparent total tract digestibility of nutrients and energy, nitrogen retention, and energy content of weaned piglets (Koo, Bustamante‐García, & Nyachoti, ). In vitro, L. plantarum is reported to protect the epithelial barrier disruption caused by enterotoxigenic Escherichia coli (ETEC) in intestinal porcine epithelial cells (Wang, Zeng, et al, ; Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Researches have shown that oral administration of L. plantarum can improve the immune responses and enhance the intestinal barrier function of weaning piglets (Wang, Ji, et al, ; Yang, Jiang, Zheng, Wang, & Yang, ). Diet with L. plantarum ‐fermented wheat also can improve the apparent total tract digestibility of nutrients and energy, nitrogen retention, and energy content of weaned piglets (Koo, Bustamante‐García, & Nyachoti, ). In vitro, L. plantarum is reported to protect the epithelial barrier disruption caused by enterotoxigenic Escherichia coli (ETEC) in intestinal porcine epithelial cells (Wang, Zeng, et al, ; Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in our study, despite enhanced protein digestibility, TP in the piglets' blood serum decreased at lower FRSM inclusions (8 and 12%) and increased gradually with higher doses, but still remained lower than in the control group. The reduced stomach pH, possibly due to the presence of Lactobacillus, might stimulate protein hydrolysis, contributing to increased CP digestibility in animals fed a diet with fermented components (Koo et al, 2018). Lactobacillus, being a valuable source of peptides and phenols, may increase peptide content and facilitate the breakdown of glucosinolates during FRSM fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to increasing the nutritional potential of rapeseed meal is subjecting it to fermentation (Koo et al, 2018). Fermentation not only enhances the bioavailability of nutrients in rapeseed meal but also stimulates the breakdown of cell wall structures, releasing and/or inducing the synthesis of various bioactive compounds, particularly antioxidants (Đorđević et al, 2010).…”
mentioning
confidence: 99%